دراسة تأثير محتوى الحصويات الخشنة في البيتون النفوذ على خصائصه الفيزيائية و الميكانيكية - شومان, فريدة (Latakia University Journal -Engineering Sciences Series, 2019)
This work examines the effect of coarse aggregate/cement ratio ( ) on the physical and mechanical properties of pervious concrete. In this work, three mixes were prepared with three ratio of ( ) (6,8 and 10 by weight), and ( ) ratio ranges from (0.42 – 0.52). Tests are carried out on hardened concrete to investigate the effect of coarse aggregate/cement ratio on the compressive strength, flexural strength absorption%, density, porosity%. Results showed that increasing the ratio from 6 to 10 for the used mixes reduces the compressive strength, flexural strength and density, on the other hand the porosity and the absorption increase with increasing ratio of for all studied mixes. It was found that the compressive strength at 45 days increased by 30% when the ratio decreased from 10 to 6 . And also the absorption and density changed when the ( ) ratio changed from 10 to 6, the density increased and the absorption decreased clearly. يهدف هذا البحث إلى دراسة تأثير نسبة الحصويات الخشنة إلى الإسمنت ( ) في البيتون النفوذ على خصائصه الفيزيائية والميكانيكية، تم لهذا الغرض دراسة ثلاث نسب وزنية من( ) هي: (10= ،8= ،6= ) مع نسبة الماء إلى الإسمنت ( ) تراوحت بين (0.52 - 0.42). أجريت الاختبارات على البيتون المتصلب لدراسة تأثير نسبة الحصويات الخشنة إلى الإسمنت ( ) على المقاومة على الضغط البسيط ومقاومة الشد بالانعطاف والامتصاص والكثافة والمسامية. أظهرت النتائج أن زيادة النسبة ( ) من 6 إلى 10 أدى إلى نقصان في الكثافة والمقاومة على الضغط البسيط ومقاومة الشد بالانعطاف، وبالمقابل ازدادت المسامية ونسبة امتصاص الماء مع زيادة النسبة ( ) للخلطات البيتونية الثلاث. فيما يتعلق بالمقاومة على الضغط البسيط بعمر 45 يوماً، فقد ازدادت المقاومة بنسبة تصل إلى 30% عندما تناقصت قيمة ( ) من 10 إلى 6. كذلك حصل تغير في قيم الامتصاص والكثافة عند الانتقال من( =10) إلى ( =6) إذ ازدادت قيمة الكثافة ونقص الامتصاص بشكل واضح.